The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1159/000490474
|View full text |Cite
|
Sign up to set email alerts
|

Trace Urine Albumin and Mortality: Kangbuk Samsung Health Study

Abstract: Background/Aims: The importance of a trace albumin on the urine dipstick test is not well known and is frequently disregarded in clinical practice. The aim of this study is to investigate the role of trace albuminuria in predicting all-cause mortality in Korean adults. Methods: In this retrospective cohort study, we analyzed 347,938 Korean adults who underwent urine dipstick test from 2002 to 2012 in a health examination program. The participants were divided into three groups according to dipstick negative, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
(17 reference statements)
0
2
0
Order By: Relevance
“…Consistently, the incident of OP in R-TrP was approximately two times higher compared with that in T-TrP. Clinical studies in recent years [ 14 - 16 ] have shown that TrP may be a risk factor for metabolic syndrome and increased all-cause mortality. Therefore, not only OP, but also TrP, may have clinical significance for cardiometabolic conditions, including kidney disease.…”
Section: Discussionmentioning
confidence: 76%
“…Consistently, the incident of OP in R-TrP was approximately two times higher compared with that in T-TrP. Clinical studies in recent years [ 14 - 16 ] have shown that TrP may be a risk factor for metabolic syndrome and increased all-cause mortality. Therefore, not only OP, but also TrP, may have clinical significance for cardiometabolic conditions, including kidney disease.…”
Section: Discussionmentioning
confidence: 76%
“…Therefore, the dipstick urine test would be helpful in clinical situations such as in EDs where routine tests require quick results or in medical environments where more accurate tests are not available. In addition, dipstick proteinuria has been reported as a predictor of mortality risk in the general population, and this prognostic significance was observed not only in higher degrees of proteinuria but also in trace proteinuria detected with the dipstick test [ 32 , 34 ]. Our data also showed that trace proteinuria was significantly associated with an increased risk of all-cause mortality.…”
Section: Discussionmentioning
confidence: 99%